378 Regulation of renal function by the peroxisome proliferator-activated receptor-alpha: A novel target for treating hypertension - Mark D Hatcher; Kathryn Sandberg; Dexter Lee (Journal of Clinical and Translational Science, 2023)
OBJECTIVES/GOALS: Approximately 37 million people in the U.S. have chronic kidney disease, which is a major risk factor for cardiovascular and end stage renal diseases. PPAR-Î±knockout (KO) mice exhibit increased renal inflammation and blood pressure. In this study, we investigated the role of PPAR-Î±in renal function in a mouse model of hypertension. METHODS/STUDY POPULATION: Male 4-month-old wild type (WT) and PPAR-Î±KO mice were instrumented with radio transmitters by artery canulation (Data Science Intl). This method minimizes stress and artifacts by avoiding the use of tethering, restraining, or anesthetizing the mice during data sampling. After recovery from surgery, we continuously measured mean arterial pressure (MAP) via radio telemetry in conscious ambulatory mice. After baseline MAP was established, vehicle (Veh; saline) or angiotensin II (Ang II) were infused using an osmotic minipump at a slow pressor dose (400 ng/kg/min) for 12 days. On day 12, we injected an intravenous bolus of fluorescin-sinistrin (3.74Âµl/g body weight) and collected 8 blood samples (20Âµl/sample) over 75 minutes to enable calculation of the glomerular filtration rate (GFR) using [GFR = I/(A/Î±+ B/ÃŸ)]. RESULTS/ANTICIPATED RESULTS: Similar to our prior observations, no significant (ns) differences in baseline MAP were observed between WT and PPAR-Î±KO mice [(mmHg): WT (n=6), 111 ± 20 vs. PPAR-Î±KO (n=6), 113 ± 10; ns] whereas after 12 days of the slow pressor effect of Ang II, MAP was increased in both strains [(mmHg): WT (n=8), 138 ± 11# vs. PPAR-Î±KO (n=8) , 156 ± 16#; #p DISCUSSION/SIGNIFICANCE: PPAR-Î±protects mice from worsening hypertension and is critical to preserving GFR during normotensive conditions. Ongoing studies are further investigating how PPAR-Î±regulates renal function. These finding suggest therapeutics designed to increase PPAR-Î±activity could have clinical benefit in chronic kidney disease.